CEPHALOMETRIC MEASUREMENTS IN SKELETAL CLASS I AND CLASS III MALOCCLUSION USING BJÖRK-JARABAK ANALYSIS - George Popa; Sorin Gheorghe Mihali; Anca Jivănescu; Remus-Christian Bratu; Silvia Izabella Pop; Dana-Cristina Bratu (Romanian Journal of Oral Rehabilitation)
Aim of the study: The aim of the study was to evaluate the cephalometric parameters from Björk-Jarabak analysis and to assess the sexual dimorphism in Caucasian adults with Class I and Class III skeletal patterns. Materials and methods: The study analysed 100 lateral cephalograms of adult patients from Western Romania, divided into skeletal Class I (ANB = 2° ± 2°) and Class III (ANB < 0°) groups, with 25 males and 25 females per group. Using AudaxCeph 5 Essentials software, Björk’s polygon angles (saddle, articular, and gonial angles) were measured, along with linear measurements (anterior and posterior cranial base length, mandibular ramus height, and mandibular body length). Results: Sexual dimorphism in Class I patients was observed in both angular (N-S-Ar and Sum of angles) and linear measurements, with males showing larger linear values and females showing greater angular measurements. In Class III patients, sexual dimorphism was limited to linear measurements, with males showing larger values. Between Class I and Class III patterns, significant differences were found in the articular angle and the ramal height, with Class III subjects showing smaller angular values, but larger linear dimensions. Class I patients demonstrated more numerous and stronger correlations between measurements compared to Class III patients. Conclusions: These differences support the growing evidence that ethnic and sexual variations play a significant role in craniofacial morphology and should be considered in clinical practice.